Analisis Pendapatan dan Biaya Terhadap Sisa Hasil Usaha (SHU) pada KSP Padat Asih - Endang Afrilika Napitupulu; Nadya Putri Rahmawati; Masnike Napitupulu; Sulha Silvia (LPPM Universitas Koperasi Indonesia, 2026)
Cooperatives play a crucial role in improving the welfare of their members through professional and transparent business management. One indicator of cooperative performance is the Operating Surplus (SHU), which is influenced by revenue and costs. This study aims to analyze revenue and costs at KSP Padat Asih and assess their impact on SHU. The method used is a quantitative descriptive approach with a case study approach, using secondary data from the cooperative's financial statements for the 2015–2019 period. The analysis was conducted by calculating the cost-to-income ratio and comparing it with SHU. The results show that KSP Padat Asih's revenue has consistently increased, primarily from loan interest, while costs have also increased, resulting in a cost-to-income ratio approaching 100%. KSP Padat Asih's SHU for 2015–2019 fluctuated due to work programs that affected revenue and costs. The main income came from member loan interest and late fines, while the largest costs came from organization and education. However, based on the national cooperative performance assessment standards (Ministerial Regulation of the Republic of Indonesia on Cooperatives and SMEs No. 06/Per/M.KUKM/V/2006), the average Return on Equity (ROE) of KSP Padat Asih was only 0.37%, far below the good standard (15–21%) and categorized as Poor (<3%). This indicates that although the cooperative has good operational resilience and administrative compliance, its profitability is still less than optimal. Therefore, new policies are needed to improve cost efficiency and optimize productive assets to strengthen the capital structure and member welfare in the future.Key Word : Savings and Loan Cooperative, Income, Expenses, Remaining Business Results (SHU), Financial Analysis